Pengembangan APE: Trashypoly Sebagai Penunjang Gaya Hidup Berkelanjutan (P5) pada Pengelolaan Sampah - Nurdyana, Yenicke Bara (Jurnal Didaktika Pendidikan Dasar, 2025)
The development of EGT was carried out because students' skills in processing waste in the school environment were still lacking. This research has developed appropriate and proper EGT products to support learning for the Proyek Penguatan Profil Pelajar Pancasila (P5). This product is named Trashypoly. This research uses the Research and Design (R&D) method with the ADDIE model. The researcher used observation and questionnaires as data collection techniques. The 16 students of 2nd at SDN Tunjung 1 Bangkalan, East Java, are the research subjects. Material and media experts are involved in product testing. Next, a limited trial was conducted to determine the feasibility and usefulness of the learning outcomes of sustainable lifestyles (P5). The worthy assessment score through media validation results was 75, material validation results were 83.33, and limited trials were 83.70. It is mean very worthy. Assessment of product usefulness through the pre-test obtained a score of 41.25, post-test 87.50, and N-gain score of 0.79 (high usefulness). This assessment concluded that the EGT: trashypoly is very worthy and valuable as a support for learning P5 on the theme of sustainable lifestyles through waste processing in elementary schools.